How do patients with Parkinson’s disease and cerebellar ataxia read aloud? -Eye–voice coordination in text reading - Terao, Yasuo; Tokushige, Shin-ichi; Inomata-Terada, Satomi; Miyazaki, Tai; Kotsuki, Naoki; Fisicaro, Francesco; Ugawa, Yoshikazu (Frontiers in Neuroscience, 2023)
Background The coordination between gaze and voice is closely linked when reading text aloud, with the gaze leading the reading position by a certain eye–voice lead (EVL). How this coordination is affected is unknown in patients with cerebellar ataxia and parkinsonism, who show oculomotor deficits possibly impacting coordination between different effectors. Objective To elucidate the role of the cerebellum and basal ganglia in eye–voice coordination during reading aloud, by studying patients with Parkinson’s disease (PD) and spinocerebellar degeneration (SCD). Methods Participants were sixteen SCD patients, 18 PD patients, and 30 age-matched normal subjects, all native Japanese speakers without cognitive impairment. Subjects read aloud Japanese texts of varying readability displayed on a monitor in front of their eyes, consisting of Chinese characters and hiragana (Japanese phonograms). The gaze and voice reading the text was simultaneously recorded by video-oculography and a microphone. A custom program synchronized and aligned the gaze and audio data in time. Results Reading speed was significantly reduced in SCD patients (3.53 ± 1.81 letters/s), requiring frequent regressions to compensate for the slow reading speed. In contrast, PD patients read at a comparable speed to normal subjects (4.79 ± 3.13 letters/s vs. 4.71 ± 2.38 letters/s). The gaze scanning speed, excluding regressive saccades, was slower in PD patients (9.64 ± 4.26 letters/s) compared to both normal subjects (12.55 ± 5.42 letters/s) and SCD patients (10.81 ± 4.52 letters/s). PD patients’ gaze could not far exceed that of the reading speed, with smaller allowance for the gaze to proceed ahead of the reading position. Spatial EVL was similar across the three groups for all texts (normal: 2.95 ± 1.17 letters/s, PD: 2.95 ± 1.51 letters/s, SCD: 3.21 ± 1.35 letters/s). The ratio of gaze duration to temporal EVL was lowest for SCD patients (normal: 0.73 ± 0.50, PD: 0.70 ± 0.37, SCD: 0.40 ± 0.15). Conclusion Although coordination between voice and eye movements and normal eye-voice span was observed in both PD and SCD, SCD patients made frequent regressions to manage the slowed vocal output, restricting the ability for advance processing of text ahead of the gaze. In contrast, PD patients experience restricted reading speed primarily due to slowed scanning, limiting their maximum reading speed but effectively utilizing advance processing of upcoming text.